Avaliação do efeito do alho (Allium sativum L.) sobre o colesterol plasmático em coelhos com hipercolesterolemia induzida - Klassa, B. [UNESP]; Grosseli, M.m. [UNESP]; Kiyomura, A.k. [UNESP]; Alves, M.j.q.f. [UNESP] (Sociedade Brasileira de Plantas Medicinais, 2013)
The use of plants to treat diseases or even to cure them is a high diffused popular tradition, and several studies discuss the therapeutic and pharmacological properties of garlic in the reduction of hyperlipidaemias. The objective of the present study was to investigate the influence of the aqueous extract of garlic (Allium sativum) to treat the serum cholesterol of rabbits with experimental hypercholesterolemia. The animals were divided into G1 (control group) and G2 (group treated with garlic). The experiment was developed according to 3 phases: during the 1st phase, all animals were provided with a regular diet to evaluate the basal cholesterol; during the 2nd phase, all animals received a supplemented diet until the end of the experiment, in order to develop hypercholesterolemia and, in the 3rd phase, the animals on G2 received the garlic treatment. The cholesterol registered on the 1st phase was 39.94 ± 9.57 mg dL-1. On the 2nd phase, there was an increase on the serum cholesterol level in both groups - higher than 100 mg dL-1. Concerning the treatment, the garlic did not reduce the serum cholesterol in rabbits.

A utilização de plantas no tratamento de doenças ou como meio curativo é uma tradição popular e altamente difundida, sendo que muitos trabalhos abordam as propriedades terapêuticas e farmacológicas do alho na redução das hiperlipidemias. O objetivo deste estudo foi investigar a influência do extrato aquoso (E.A.) do alho (Allium sativum L.) no tratamento do colesterol plasmático em coelhos com hipercolesterolemia experimental. Os animais foram divididos em G1 (grupo controle) e G2 (grupo tratado com alho). O experimento foi desenvolvido em três fases: na 1ª fase os animais receberam dieta comercial de coelhos para avaliar o nível basal de colesterol nos animais; na 2ªfase, todos os animais passaram a receber dieta suplementada com gema de ovo, até o final do experimento, para desenvolver hipercolesterolemia, e; na 3ª fase os animais do grupo G2 receberam o tratamento com E. A. de alho. O colesterol na 1ª fase foi de 39,94 ± 9,57 mg dL-1. Na 2ª fase houve elevação significativa (p<0,05) no nível de colesterol plasmático nos dois grupos -acima de 100 mg dL-1. Com relação ao tratamento, o alho não promoveu redução no colesterol plasmático dos coelhos, contrapondo os dados da literatura.
Evaluation of garlic (Allium sativum L.) effects on the serum cholesterol of rabbits with induced hypercholesterolemia
Keywords: Allium sativum; alho; coelho; hipercolesterolemia; Allium sativum; garlic; hypercholesterolemia; rabbits